Psychological Demands of International Rugby Sevens and Well-Being Needs of Elite South African Players - Ninette Kruyt; Heinrich Grobbelaar (Frontiers in Psychology, 2019)
Rugby sevens was included in the 2016 Olympic Games, with South Africa’s Blitzboks winning bronze. They also won the 2016/2017 and 2017/2018 World Rugby Sevens Series. Whilst peak performance is paramount at the elite level there is a growing responsibility to address player well-being and off-the-field player needs. This study explored the psychological demands of international rugby sevens and the well-being needs of elite players. Twenty professional players (age range: 21–33 years) participated in semi-structured interviews. Qualitative content analysis yielded five categories of psychological demands: (1) tournament structure, (2) resilience, (3) cope with physicality, (4) perform when fatigued, and (5) perform under pressure. The prevailing team culture included: (1) team cohesion, (2) clear purpose, (3) work ethic, (4) team values, (5) happy environment, (6) relationships with coaching staff, and (7) faith. Various psychological skills [(1) goal-directed behavior, (2) compartmentalization, (3) deal with anxiety, (4) motivation, (5) imagery, and (6) self-confidence] and mental strategies [(1) coping, (2) “back-to-zero,” (3) creativity, and (4) cognitive triggers] utilized by the players are discussed. Their general well-being and individual needs were: (1) physical needs, (2) financial concerns/needs, (3) preparation for life after rugby career, (4) support structures, and (5) mental (ill) health. This information could be useful to develop an integrated sport psychological and well-being program aimed at improving performance and facilitating psychological well-being both during and after retirement from elite sport.